"It was the whole picture" a mixed methods study of successful components in an integrated wellness service in North East England - M. Cheetham; P. Van der Graaf; B. Khazaeli; E. Gibson; A. Wiseman; R. Rushmer (BMC, 2018)
Abstract Background A growing number of Local Authorities (LAs) have introduced integrated wellness services as part of efforts to deliver cost effective, preventive services that address the social determinants of health. This study examined which elements of an integrated wellness service in the north east of England were effective in improving health and wellbeing (HWB). Methods The study used a mixed-methods approach. In-depth semi-structured interviews (IVs) were conducted with integrated wellness service users (n = 25) and focus groups (FGs) with group based service users (n = 14) and non-service users (n = 23) to gather the views of stakeholders. Findings are presented here alongside analysis of routine monitoring data. The different data were compared to examine what each data source revealed about the effectiveness of the service. Results Findings suggest that integrated wellness services work by addressing the social determinants of health and respond to multiple complex health and social concerns rather than single issues. The paper identifies examples of 'active ingredients' at the heart of the programme, such as sustained relationships, peer support and confidence building, as well as the activities through which changes take place, such as sports and leisure opportunities which in turn encourage social interaction. Wider wellbeing outcomes, including reduced social isolation and increased self-efficacy are also reported. Practical and motivational support helped build community capacity by encouraging community groups to access funding, helped navigate bureaucratic systems, and promoted understanding of marginalised communities. Fully integrated wellness services could support progression opportunities through volunteering and mentoring. Conclusions An integrated wellness service that offers a holistic approach was valued by service users and allowed them to address complex issues simultaneously. Few of the reported health gains were captured in routine data. Quantitative and qualitative data each offered a partial view of how effectively services were working.